Exploratory study on intellectual capital and the market capitalisation - assest book value gap: the case for the singapore equity market. - Yap, Wee Kwong. (2008)
This dissertation assesses if investors assign a premium to the intellectual capital held by companies listed on Singapore Stock Exchange, as demonstrated by the quantifiable gap between market capitalisation and book value of those companies’ equity for 45 STI component stocks for the period between 1990 to 2003.